Can Anti-Thyroid Antibodies Influence the Outcome of Primary Chronic Immune Thrombocytopenia in Children? - Giordano, Paola; Delvecchio, Maurizio; Lassandro, Giuseppe; Valente, Federica; Palladino, Valentina; Chiarito, Mariangela; Wasniewska, Malgorzata; Faienza, Maria F. (Endocrine, Metabolic & Immune Disorders-Drug Targets, 2020)
Background: Immune thrombocytopenia (ITP) is an acquired immune mediated disorder characterized by isolated thrombocytopenia. Pediatric ITP patients can develop autoantibodies such as anti-thyroglobulin (TG) and anti-thyroperoxidase (TPO), even in the absence of clinical signs of autoimmune disease. Objective: The purpose of this article is to provide a review about: 1) the prevalence of positivity of anti-thyroid antibodies (TPO and TG) in pediatric patients with chronic ITP; 2) the role of autoimmune thyroiditis on the outcome of chronic ITP. Methods: The authors individually completed a review of the literature for this article. Retrospective and prospective clinical studies with pediatric cohorts were considered. Results: From the analysis of data, we found 4 papers which included studies only on pediatric population, and which corresponded to selected criteria. Pediatric ITP patients have been shown to have a statistically significant prevalence of anti-thyroid antibodies over healthy controls (11.6-36% versus 1.2-1.3%). No correlation has been found between the platelet count and the prevalence of positive anti-thyroid antibodies at any time of the follow up. Conclusion: The results of our bibliographic research demonstrated that: a) pediatric patients with chronic ITP tend to have a statistically significant prevalence of anti-thyroid antibodies positivity respect to general pediatric population; b) there are no clear data about the role of autoimmune thyroiditis as prognostic factor for chronic course of ITP in pediatric age.
Keywords: anti-thyroglobulin